Intervening conditions of the implementation of an Advanced Access Model: an implementation research - Lislaine Aparecida Fracolli; Larayne Gallo Farias Oliveira; Thaynara Silva dos Anjos; Stephen Timmons; Lúcia Yasuko Izumi Nichiata; Anna Luiza de Fátima Pinho Lins Gryschek; Alexandre Ramiro Pinto (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify the conditions that interfere with the implementation of the Advanced Access model in primary health care. Method: This is an implementation research that used the Consolidated Framework for Implementation Research (CFIR). The CFIR provides a classification of factors that affect the implementation of a technology and comprises five domains: characteristics of the intervention, external environment, internal environment, individuals, and process. The study setting included 13 Health Units in the southern region of the city of São Paulo-SP. 39 health professionals and 10 managers participated. Data was collected through semi-structured interviews. These were recorded and transcribed, and the text data was coded based on pre-established codes derived from the CFIR domains. Results: Four categories were found that impacted the implementation of the AA model in services: 1) Characteristics of the Advanced Access model that impacted implementation; 2) Organization of the health sector and the Advanced Access model; 3) Characteristics of the individuals involved in the innovation; and 4) The planning and leadership model for implementation. Final Considerations: The social, structural, and professional conditions in the municipality of São Paulo made it difficult to implement the AA model. The implementation research supported the process of improving access in the health units studied and provided evidence of what helped and what hindered the restructuring of the access model in these places.